Construction of Volume Tables-a Generalised Approach - Unnikrishnan, K. P.; Singh, Ravendra (Indian Forester, 1984)
The present paper outlines the development of a volume table construction method based upon statistical principles. It lays special emphasis to the usual conditions which underlie the theory of regression and how these can be met in finding out best fit volume equations. Description of a computer program developed on these lines and finalised for 'System-332', Computer is an added feature. Stand table and volume tables constructed for sample data for the species Diperocarpus indicus have been included in the paper.